Metal-free, low-cost, and high-performance membraneless ethanol fuel cell - Ali, M. A.; Sedenho, G. C.; Pacheco, J. C.; Iost, R. M.; Rahman, A.; Hassan, A.; Crespilho, F. N.
Renewable energy conversion from biomass in fuel cells can mitigate the imbalance between the carbon sequestration and sustainable energy demands. Ethanol biofuel cells based on NAD-dependent alcohol dehydrogenase (ADH)as catalyst are suitable alternatives; however, metal-free electrodes are still not effective for achieving a satisfactory power density. We report a membraneless and metal-free ethanol-O2 biofuel cell that is entirely composed of organic and biological molecules. The biofuel cell is based on a redox-active quinone-based catalyst produced by one-pot synthesis that operates efficiently with high power density (264 mW m?2), at mild conditions of pH and room temperature. The cost of this biofuel cell is more than 2.5-fold lower than that of a conventional system with a Pt-based electrocatalyst, potentially enabling cost-effective production of renewable electricity.
Keywords: ETHANOL-O2 FUEL CELL; METAL-FREE CATALYST; NAD-DEPENDENT ALCOHOL DEHYDROGENASE; BIOELECTROCATALYSIS; IN SITU EPR SPECTROSCOPY